IMPROVING STUDENT LEARNING OUTCOMES USING THE JIGSAW TYPE COOPERATIVE LEARNING MODEL IN SCIENCE LESSONS ON THE RESPIRATORY SYSTEM MATERIAL HUMANITY IN CLASS V SDKr. MUTIARA KASIH STUDENTS - Farida, Lidia; Suyanto, Suyanto (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
Education is an essential requirement for individuals, leading to continuous efforts in enhancing the quality of education to produce highly skilled human resources. One of these efforts involves implementing the Jigsaw type Cooperative Learning Model, which aims to develop students' precision and cooperation skills during group discussions. The objective of this study is to assess the responses and learning outcomes of fifth-grade students in the science subject, specifically on the human digestive system, using the Jigsaw type cooperative learning model. This research adopts a quasi-experimental approach with a Pretest Posttest Control Design. The study population consists of fifth-grade students at SDKr Mutiara Kasih, and the sample is determined using a saturated sampling technique, resulting in a sample size of 16 students. Data collection methods include observation, tests, questionnaires, and documentation. The independent variable in this research is the Jigsaw type cooperative learning model, while the dependent variable is the students' learning outcomes in science, specifically on the Human Digestive Equipment material. The data analysis technique employed in this study is the N-Gain test. The findings of this research demonstrate that the demonstration learning method has a significant impact on the learning outcomes of fifth-grade students at SDKr Mutiara Kasih. Furthermore, there is a notable difference in the influence between demonstration learning and conventional learning in the science subject for fifth-grade students.